PEMBENTUKAN KOMUNITAS SAHABAT PEDULI HIPERTENSI UNTUK MENINGKATKAN KEPATUHAN MENJALANI HIDUP SEHAT DI PUSKESMAS SAKO PALEMBANG - Simamora, Sarmalina; Sonlimar Mangunsong; Mona Rahmi Rulianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
The highest number of hypertension patients in South Sumatra is in Palembang. This disease is the leading cause of premature death among non-communicable diseases. Therefore, the government has set its control as a key target, aiming for 90% of hypertensive patients undergoing treatment to achieve controlled blood pressure. Sako Community Health Center has several non-communicable disease (NCD) posts, one of which is located in RT 26, Sako Subdistrict. Activities are conducted once a month at the neighborhood head's house. Services at the post are assisted by community health volunteers (kaders). The goal of the program is to enhance the ability of these volunteers to assist hypertensive patients in managing their blood pressure. This is achieved through the formation of a community called